Valuation of non-life liabilities from claims triangles - Mathias Lindholm; Filip Lindskog; Felix Wahl (Risks, 2017)
This paper provides a complete program for the valuation of aggregate non-life insurance liability cash flows based on claims triangle data. The valuation is fully consistent with the principle of valuation by considering the costs associated with a transfer of the liability to a so-called reference undertaking subject to capital requirements throughout the runoff of the liability cash flow. The valuation program includes complete details on parameter estimation, bias correction and conservative estimation of the value of the liability under partial information. The latter is based on a new approach to the estimation of mean squared error of claims reserve prediction.
Keywords: 330; liability valuation; claims triangles; cost of capital; parameter estimation; parameter uncertainty